Polyindole-Au nanocomposite produced at the liquid/liquid interface - Joshi L.; Prakash R. (My University, 2025)
This letter is a continuation of our previous work on synthesis of polyindole-gold nanocomposite published in this journal. In the present work, we have synthesized the similar hybrid organo-inorganic composite using a novel interfacial polymerization route at water/dichloromethane interface. The hybrid organo-inorganic composite material is based on conducting polymer, polyindole and gold nanoparticles; the redox character of indole (monomer) and chloroauric acid facilitates the polymerization of monomer. Entirely different morphological and structural features are observed compared to our previous results. The contact of monomer and metal salt acid (chloroauric acid) at the interface results in the formation of polyindole-Au nanocomposite (without any need of template or capping agent) of nanorod morphology encapsulating Au nanoparticles. XRD studies shows semi-crystalline nature of the polymer unlike the amorphous polyindole formed using other methods. Tunable photoluminescence spectra show the potential applications of the composite in the field of organic laser and organic optoelectronics. © 2011 Elsevier B.V.